A nutrition-sensitive circular bioeconomy for food systems transformation in Africa - Abe-Inge, Vincent; Aidoo, Raphael; Kwofie, Ebenezer Miezah; Ulimwengu, John M. (AKADEMIYA2063, 2024)
Africa’s commitment to creating a sustainable and self-sufficient economy for its rapidly growing population has led to programmatic actions aimed at meeting local food, energy, and material demands sustainably and without compromising planetary boundaries (Africa Business Page 2022; Agri SA 2023). The bioeconomy has become a primary focus of this transformative blueprint, generally positioned as a vehicle for generating and using bioresources in meeting local demands for abundance, sustainable goods, and services (Gatune, Ozor, and Oriama 2021; Malabo Montpellier Panel 2022). However, the implementation momentum of the bioeconomy is incumbent on a well-planned and objective-oriented policy framework that supports generation of scientific evidence and reasonable investment structures, among other requirements for implementation (East African Community 2022; Pachón et al. 2018).